Effect of Rare Earth on Inclusions and Fatigue Properties of 20CrMnTi Gear Steel - Wang Li, Liu Chengbao, Li Haoqiu, Wang Yi, Sun Zonghui, Liu Chunwei, Yang Chaoyun, Fu Zhihao (Teshugang)
To deeply investigate the effect of rare earth （La/Ce） on inclusions and fatigue properties of 20CrMnTi gear steel， the inclusions in 20CrMnTi and 20CrMnTi-RE gear steel treated with 0.002 7% rare earth were analyzed and characterized by various analytical and testing methods， the change of fatigue property was compared and analyzed. The ultra-high weekly fatigue test was carried out and analyzed the change of fatigue properties.The results show that rare earth can react with O element in gear steel to form rare earth oxides， and co-exist with other inclusions such as CaS and MgAl2O4， which become the core of TiN， the complex phase of CaS-MgAl2O4-（MnS）-TiN is transformed into the complex phase of CaS-MgAl2O4-（MnS）-RE2O3-TiN. After addition of rare earth， the amount of inclusions in 20CrMnTi steel decreased significantly， and the inclusions with size over 30 μm basically disappeared. In addition， rare earth improves the anti-fatigue property of gear steel. The fatigue limit of gear steel with rare earth is 26.6 MPa higher than that of gear steel without rare earth at the condition of 50% failure probability for 107 cycles， with better anti-fatigue performance.